Sosialisasi pembuatan produk kesehatan jamu instan dan teh kombucha sebagai peluang ekonomi bagi masyarakat Dusun Cukal Desa Bendosari - Sari, Yulia Anita (Maliki Interdisciplinary Journal, 2023)
Bendosari Village is one of the areas located in Malang Regency, precisely in Pujon District. Bendosari Village is located on the slopes of Mount Kawi. Especially in Dusun Cukal. Based on the geographical location, many people in this village use the existing land for agriculture and plantations. There are several reasons underlying the implementation of this socialization, namely the use of fertile land in this hamlet as Asman Toga (Independent Care of Family Medicinal Plants). From the results of Asman Toga, it can be used as a business opportunity for the surrounding community, such as the turmeric rhizome plant which can be used as an alternative source of herbal medicine which is packaged in a more modern and instant way. Then there is also Kombucha Tea Farming which can be used as a substitute for everyday tea, because the benefits of this pharmaceutical tea are very many, one of which is for the body’s metabolism and digestion. Therefore, it is necessary to socialize the manufacture of instant herbal medicine and kombucha pharmaceutical tea as a business opportunity for the local community, which can increase people’s daily income.